The impact of risk management functions and professional training on enterprise risk management and organizational continuity of performance in the UAE Ministry of Interior - Alkaabi, Mohamed Matar Saleh Sulaiman (2025)
This study was an exploratory investigation into the impact of various risk management factors on enterprise risk management, and the subsequent influence on employees' performance and organisational continuity of performance within the Ministry of Interior in the United Arab Emirates (UAE). The research was guided by the theoretical framework of strategic management theory, proposing a conceptual model that connects four risk management factors (risk identification, risk assessment, risk response, and risk monitoring and reporting), enterprise risk management, employees' performance, organisational continuity of performance, and professional training. The study focused on a specific population of 214 middle to top management staff members in the UAE Ministry of Interior, with the sample selected through stratified random sampling. Analysis techniques included structural equation modelling using SmartPLS 3 software, along with bootstrapping for significance testing. The data was meticulously screened, ensuring adherence to the assumptions of normality, linearity, homoscedasticity, and absence of multicollinearity. The findings provided robust support for all hypothesised relationships in the conceptual framework, indicating a significant influence of the risk management factors on enterprise risk management, and in turn, on employees' performance and organisational continuity of performance. Furthermore, the results underscored the importance of professional training as a significant moderator, reinforcing the influence of enterprise risk management on the performance dimensions. Based on these findings, the study recommends the ministry to intensify its focus on risk management practices, and to invest in professional training to improve both employee performance and organisational continuity of performance. For future studies, the research suggests a comparative investigation between public and private sectors, inclusion of more influencing variables, examination of other potential moderators, a longitudinal study design, the use of alternative data collection methods, and exploration of intervention effects to broaden the current understanding in the field.